Pengaruh Penggunaan Al Generatif Terhadap Physics Learning Anxiety dan Motivasi Belajar Peserta Didik - Rasyid, Juniar; Mawardi Jalil Masri; Sulfianty; Nurul Amalia Aris (Charm Sains: Jurnal Pendidikan Fisika, 2026)
Physics learning anxiety is one of the psychological factors that influences the motivation and physics learning outcomes of high school students. This study aims to analyze the effect of generative AI use on students’ physics learning anxiety and learning motivation. The research employed a quasi-experimental method with a pretest–posttest control group design involving 60 high school students divided into experimental and control groups. The experimental group participated in learning activities using generative AI, while the control group received conventional instruction. The research instruments consisted of a physics learning anxiety questionnaire and a learning motivation questionnaire that had been tested for validity and reliability. Data were analyzed using appropriate statistical tests. The results show that the use of generative AI significantly reduces students’ physics learning anxiety and increases their learning motivation compared to conventional learning. These findings indicate that generative AI is effective as a learning medium that can reduce learning anxiety and enhance students’ motivation, and it has implications for its use as an innovative and adaptive learning medium in physics education.